Accountability and Transparancy of APBDes Management in Batu Putih Village - Lilis Wahyu Ningsih; Iskandar Sam; Ratih Kusumastuti (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze accountability and transparency in the management of the Village Revenue and Expenditure Budget (APBDes) in Batu Putih Village, Pelawan District, Sarolangun Regency. The method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the management of the APBDes has been carried out according to the stages set out in the regulations, namely planning, implementation, recording, reporting, and accountability. Accountability is reflected in the obligation of the village government to prepare financial reports in a timely manner. Meanwhile, transparency can be seen from efforts to convey information to the public, although it is still limited to certain media and has not reached all levels of society. Community participation in the planning process also still needs to be improved. In conclusion, village financial management is quite good, but it needs to be improved in terms of public involvement and openness of information to realize a transparent and responsible village government.